2012
DOI: 10.1007/s10409-012-0049-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of modeling unsteady blade row interaction in a transonic compressor stage part 1: code development and deterministic correlation analysis

Abstract: The average-passage equation system (APES) provides a rigorous mathematical framework for accounting for the unsteady blade row interaction through multistage compressors in steady state environment by introducing deterministic correlations (DC) that need to be modeled to close the equation system. The primary purpose of this study is to provide insight into the DC characteristics and the influence of DC on the time-averaged flow field of the APES. In Part 1 of this two-part paper, firstly a 3D viscous unstead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…From the above analysis it is inferred that, the distributions of deterministic stress and deterministic enthalpy are quite different from that in compressors [25]. Usually in compressors, the deterministic stress and enthalpy have large magnitudes at the rotor-stator interface and decrease rapidly in the flow direction downstream of the interface; however, there is no obvious similar behavior in the turbine.…”
Section: Deterministic Stress/enthalpy Studymentioning
confidence: 84%
See 1 more Smart Citation
“…From the above analysis it is inferred that, the distributions of deterministic stress and deterministic enthalpy are quite different from that in compressors [25]. Usually in compressors, the deterministic stress and enthalpy have large magnitudes at the rotor-stator interface and decrease rapidly in the flow direction downstream of the interface; however, there is no obvious similar behavior in the turbine.…”
Section: Deterministic Stress/enthalpy Studymentioning
confidence: 84%
“…Modeling deterministic correlations is the key to close the average-passage equation system which could provide a rigorous mathematical framework for accounting for the unsteady blade row interaction in steady state calculation by introducing deterministic correlations. Liu et al [24,25] studied the deterministic stress and enthalpy correlations in compressors, which could be valuable for modeling deterministic correlations. However, few studies focused on deterministic correlations in turbines.…”
Section: Introductionmentioning
confidence: 99%
“…et al that, in general, unsteady simulation is recommended to compute at least 10 to 20 time steps per period. To obtain a more accurate result, 20 steps per passage were chosen [38]. Hence, 300 steps were able to cover a whole period of impeller revolution.…”
Section: Discretization Methods and Boundary Conditionsmentioning
confidence: 99%
“…Hence, more research work for modeling the DC should be conducted. In our previous studies, the distribution characteristics of DC and the effects of DC on time-averaging simulation were conducted [12][13][14][15][16]. We found that the timeaveraging simulation with axisymmetric DC can take into account the major part of the unsteady effects on spanwise redistribution.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, many efforts have been made and some DC models have been proposed [3][4][5][6][7][8][9][10][11]. Some DC models [3][4][5]8] are axisymmetric based on a hypothesis that the purely unsteady fluctuations are negligible, though the DC is not uniform in circumferential direction and the gradients are large in some regions in the blade passage [12]. Adamczyk et al [3] proposed the first model using overlapping grids for all blade rows without the interface planes.…”
Section: Introductionmentioning
confidence: 99%